2007
DOI: 10.1016/j.drudis.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptors in drug discovery

Abstract: SummaryOrphan nuclear receptors provide a unique resource for uncovering novel regulatory systems that impact human health and provide excellent drug targets for a variety of human diseases. Ligands of nuclear receptors have been used in a number of important therapeutic areas, such as breast cancers, skin disorders, and diabetes. Orphan nuclear receptors, therefore, represent a tremendous opportunity in understanding and treating human diseases. This review highlights advances and potentials of using orphan n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 74 publications
0
55
0
1
Order By: Relevance
“…Because nuclear receptors are important regulators of human physiology and pathology, ligands that interact with nuclear receptors to modulate the activity of the receptors have direct implications in therapy using drugs (33). The ligands of nuclear receptors have been used in many important clinical areas, for example, the estrogen receptor antagonist, tamoxifen, is currently used in the treatment of breast cancers (34).…”
Section: Discussionmentioning
confidence: 99%
“…Because nuclear receptors are important regulators of human physiology and pathology, ligands that interact with nuclear receptors to modulate the activity of the receptors have direct implications in therapy using drugs (33). The ligands of nuclear receptors have been used in many important clinical areas, for example, the estrogen receptor antagonist, tamoxifen, is currently used in the treatment of breast cancers (34).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of P-gp is predominantly controlled by the pregnane X receptor and constitutive and rostane nuclear receptors (Cervenyet al 2007). These two receptors could be classified as adopted orphan receptors with a specific ligands (including VCR Breier et al 2013b) identified in recent years (Shi 2007) and are dimerization partners of retinoid X receptors (Saeki et al 2010) with known ligand 9-cis retinoic acid (Brtko and Thalhamer 2003;Brtko and Dvorak 2011). Interestingly, the role of regulatory pathway of nuclear receptors for retinoids in development of P-gp-mediated MDR could take part (Sulova et al 2008(Sulova et al , 2012Breier et al 2014).…”
Section: Mdr1→mentioning
confidence: 99%
“…Interestingly, the role of regulatory pathway of nuclear receptors for retinoids in development of P-gp-mediated MDR could take part (Sulova et al 2008(Sulova et al , 2012Breier et al 2014). Nestin was assumed to be transcriptionally controlled by the orphan receptor Nurr1 (Kappen and Yaworsky 2003), which the ligands are currently unknown (Shi 2007). To determine the mechanism that VCR induces coexpression of P-gp and nestin in MOLM-13 and SKM-1 cells as well as to determine the role for this coexpression in the development of P-gp-mediated multidrug resistance, further research is necessary.…”
Section: Mdr1→mentioning
confidence: 99%
“…48 members of NR superfamily can be subdivided into three major categories, namely, the endocrine nuclear receptors, adopted orphan receptors, and orphan receptors such as NR4A for which cognate ligands have not yet been identified. The NR4A orphan receptor subfamily includes NR4A1 (Nur77, NGFI-B,TR3), NR4A2 (Nurr1, NOT), and NR4A3 (Nor-1, MINOR) [17,18,19,20] , and it has been suggested that the failure to identify an endogenous ligand may be due to the lack of a typical NR ligand binding pocket in the LBD domain of Nurr1 or NR4A2 receptors [21] . Instead, Nurr1 are immediate early genes whose expression is induced by various stimuli including cyclic AMP, growth factors, inflammatory signals, and hormones [17] .…”
Section: Nuclear-hormone Receptorsmentioning
confidence: 99%